(untitled) (International relations and international law Journal, 2018)
The problem of food safety has been one of the most pressing issues for many centuries. But over the last three decades this issue has become more acute. Today unsafe foods represent not only a huge danger to everyone’s health, but also one of the most important global threats to healthcare and food security. Therefore, ensuring food safety is one of the main factors determining people’s health, and the most important task and responsibility of all States and the world community as a whole. The main purpose of this research is to study the international legal experience of the ensuring food safety on the example of the two largest regional integration associations-the European Union and the Eurasian economic Union. As part of this study, the food legislation of the EU and the EAEU was considered, as well as a comparative analysis of the most important provisions and parameters of the main legal documents in this area with the use of the synchronic method of comparative research. In order to obtain more detailed and reliable information on the issues of the studied topic, the article considered various scientific works and studies of many foreign, domestic and Russian scientists, as well as guides, collections, brochures and guidance materials of such international and national organizations as FAO, WHO, IFC and «KAZNEX INVEST». As a result, the study identified the main differences and similarities, as well as the advantages and disadvantages of the two food laws. Given the fact that the problem of food safety covers the interests of everyone and all countries of the world, to date, there is not much studies devoted to the international legal and comparative analysis of regulatory documents of the EU, the EAEU and the Republic of Kazakhstan, regarding food safety. Therefore, this research article will allow to get acquainted not only with the basic legal framework, but also the basic requirements of the EU and the Eurasian economic Union in ensuring food security. Key words: food safety, the European Union, the EAEC, food.